Adhesion improvement of thick DLC coatings produced by cathodic arc evaporation over stainless steel using carbon bombardment step. - Mazuco, Felipe de Sousa (2021)
The main restriction in the application of thick hydrogen-free amorphous carbon (a-C) coatings is the adhesion to the substrate, since high compressive stresses tend to delaminate the coating when a certain thickness is reached. In the present work, amorphous carbon films were deposited by unfiltered cathodic arc over a gas nitrided stainless steel substrate with metallic chromium as bond layer. An additional step was included, where carbon ions were accelerated by high bias potential before the deposition of functional a-C, to produce a carbon transition layer to act as a buffer layer. During a preliminary analysis, different thicknesses of this transition layer were produced, including a sample without this step, for reference purposes. The coating adhesion was evaluated by scratch test. In addition, the microstructure of the interface was analyzed by scanning transmission electron microscopy (STEM) and the sp-type bonds were quantified by electron energy loss spectroscopy (EELS). The analysis of the microstructure close to the interface with the chromium bond layer revealed a mixing layer of Cr and C. Furthermore, it was observed the formation of the transition layer characterized by a homogeneous carbon layer with high sp2 content, when compared to the functional amorphous carbon layer. Results indicate a significant enhancement of adhesion for the samples prepared with the carbon bombardment step, which can be correlated to the presence of the mixing layer and the carbon transition layer. Moreover, a decrease in adhesion was observed for an increase in the thickness of the transition layer, which can be attributed to the lower shear strength of this sp2 rich layer. In a second phase, three sets of experiments were designed to optimize the carbon bombardment step. The parameters studied were the duration combined with the bias voltage, the cathode current and the temperature. It was found that not only the thickness of the carbon transition layer is important for the adhesion but also the sp3 content. For instance, a lower bias voltage was able to increase the sp3 content of the carbon transition layer mitigating the negative impact of a thicker carbon transition layer. Also, an increase in the carbon cathode current could increase the adhesion possibly by extending the mixing layer. Finally, the best adhesion result was achieved when the substrate temperature of the bombardment was reduced. The most probable cause for that is a compositional modification in the mixing layer, like a change in the carbides formed in that region.